SIMULASI SISTEM REGENERATIVE BRAKING PADA PENGONTROLAN KECEPATAN MOTOR DC BERBASIS AUTO-TUNING FUZZY-PID - Arghanata Cahya Nugraha; Mochammad Rusli; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2022)
Air pollution from motor vehicle fumes has become a big problem for the environment. The existence of electric vehicles is an effort to reduce the problem of air pollution. However, electric vehicles that use battery resources have a weakness in battery lifetime. To overcome this, we need a system where the battery life when used so as not to run out quickly, namely with a regenerative braking system. Simulation of the regenerative braking system for controlling a DC motor based on fuzzy-PID auto-tuning is a simulation of the regenerative braking system using a bidirectional DC-DC converter and controlling it using auto-tuning fuzzy-PID. This system simulation aims to obtain appropriate control with the system and determine changes in the SOC value of the battery from the resulting regenerative braking. From the system simulation results, it can be seen that the actual speed of the DC motor and changes in the SOC value of the battery can be seen by knowing the value of the performance parameters of the controls made. Index Terms— electric vehicle, regenerative braking, bidirectional dc-dc converter, DC motor, auto-tuning fuzzy-